Pengembangan Media Pembelajaran Smart Train PAUD Berdasarkan Prinsip Reuse - Antika, Dewi Hajar Windi; Hartono; Setiawan, Deni (Pendidikan Guru PAUD Universitas Persatuan Guru Republik Indonesia Semarang, 2025)
Using used materials to create learning materials is one effective way to stimulate creativity in young children. This study aims to evaluate how to develop tools that can encourage creativity in early childhood. In this study, the approach applied is through document studies involving 19 documents related to reuse principle. The selection of documents in this study focuses on documents from Indonesia published in the last decade. The findings literature analysis indicate a need to create learning media that can stimulate the creativity of children at an early age to produce meaningful learning and working experiences. This also emphasizes the importance of developing learning media that can increase creativity students at early age. This media will be very useful for young children. This media is very suitable as an alternative for teachers in increasing students' creativity, by considering the development and characteristics of each child. Researchers have the opportunity to create teaching materials support the creativity of children at an early age by utilizing other used teaching materials, and it is hoped that the results of this study can be used as a reference for further research, especially development of teaching materials from used materials.